2023
DOI: 10.1186/s13071-023-05778-1
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection of dengue and Zika viruses mutually enhances viral replication in the mosquito Aedes aegypti

Abstract: Background The mosquito Aedes aegypti transmits two of the most serious mosquito-borne viruses, dengue virus (DENV) and Zika virus (ZIKV), which results in significant human morbidity and mortality worldwide. The quickly shifting landscapes of DENV and ZIKV endemicity worldwide raise concerns that their co-circulation through the Ae. aegypti mosquito vector could greatly exacerbate the disease burden in humans. Recent reports have indicated an increase in the number of co-infection cases in exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Further investigations are warranted to elucidate the intricate interplay between these two viruses. A recent study also conducted DENV (serotype 2) and ZIKV sequential coinfection in A. aegypti [88]. One of their findings is consistent with our own observations as ZIKV-infected A. aegypti strongly suppressed the replication of subsequently infected DENV (group ZIKV !…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 89%
See 2 more Smart Citations
“…Further investigations are warranted to elucidate the intricate interplay between these two viruses. A recent study also conducted DENV (serotype 2) and ZIKV sequential coinfection in A. aegypti [88]. One of their findings is consistent with our own observations as ZIKV-infected A. aegypti strongly suppressed the replication of subsequently infected DENV (group ZIKV !…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 89%
“…A recent study also conducted DENV (serotype 2) and ZIKV sequential coinfection in A . aegypti [ 88 ]. One of their findings is consistent with our own observations as ZIKV-infected A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peculiarly, Aedes aegypti mosquitoes have been extensively studied, revealing that this mosquito species can harbor hosts and vectors for both viruses in vitro settings [ 16 , 17 ]. Lin and colleagues (2023) further demonstrated that simultaneous infection with DENV and Zika virus in Aedes aegypti could intensify viral replication within the mosquito [ 18 ]. This enhanced replication capacity, alongside the mosquito’s ability to transmit multiple viruses, raises critical questions regarding the potential for human infection resulting from successive exposures to mosquitoes carrying DENV, CHIKV, or both.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that co-infection with ISV could also facilitate subsequent arbovirus infections by reducing the activity of iRNA with their sfRNA, this could also help to evade response through vDNA. On the other hand experimental co-infections with two arbovirus (DENV2 and ZIKV) have shown mutual enhancement, mediated by the non-structural protein NS5 (Lin et al, 2023 ).…”
Section: Mosquitoes and Arbovirusmentioning
confidence: 99%